Role Model Pembelajaran Kooperatif Jigsaw Melalui Filsafat Pendidikan Islam - Ning Mukaromah; Akhmad Saifulloh Azzamzuri (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2023)
A teacher who is still primarily focused on themselves is to blame for the less effective learning process. Problems arise as a result of this, according to numerous perspectives of educators. Some of the outcomes cause students to take a passive role in their education. This study is one step in a larger investigation on how best to apply learning theories, techniques, and strategies. This study employs a descriptive quantitative methodology using procedures for gathering data from surveys and interviews. Online surveying was done using a Google form. The study's findings regarding the application of the jigsaw-type cooperative learning role model in Islamic Education Philosophy courses revealed that students believed it was very interesting and not boring, and that it could assist students in finding solutions to issues during lectures. A discussion-based learning environment was also mentioned by students, who felt that their relationship with the professor was less personal as a result of their reluctance to voice their thoughts. And some other students are courageous enough to voice their opinions. Some students, among others, completed the assignment with complete accountability.